2008
DOI: 10.1159/000148646
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma S100A12 (EN-RAGE) Levels in Hemodialysis Patients with Atherosclerosis

Abstract: Background: S100A12, also known as EN-RAGE (extracellular newly identified receptor for advanced glycation end products binding protein) is a ligand for RAGE, and has been proposed to contribute to the development of atherosclerosis. In this study, we examined the plasma S100A12 concentration in patients with ESRD and undergoing hemodialysis (HD) and evaluated the relation between S100A12 level and carotid intimal media thickness (IMT) by ultrasound. Methods: We measured plasma S100A12 concentration in 72 HD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
82
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 67 publications
10
82
1
Order By: Relevance
“…However, we did not find a reduction in EN-RAGE levels after calcitriol treatment; in fact, we observed an increase. The sRAGE levels we detected were similar to those in previous reports (Kalousova et al 2006;Nakashima et al 2010), although our EN-RAGE levels were relatively higher than those previously reported (Mori et al 2009;Nakashima et al 2010;Shiotsu et al 2011;Zakiyanov et al 2011). The precise reason for such discrepancy is not clear.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, we did not find a reduction in EN-RAGE levels after calcitriol treatment; in fact, we observed an increase. The sRAGE levels we detected were similar to those in previous reports (Kalousova et al 2006;Nakashima et al 2010), although our EN-RAGE levels were relatively higher than those previously reported (Mori et al 2009;Nakashima et al 2010;Shiotsu et al 2011;Zakiyanov et al 2011). The precise reason for such discrepancy is not clear.…”
Section: Discussionsupporting
confidence: 90%
“…Elevated plasma EN-RAGE concentrations have been positively associated with carotid artery atherosclerosis (Mori et al 2009;Kim et al 2012), and Nakashima et al showed that EN-RAGE concentration was a direct predictor of allcause and CVD-related mortality, even after adjusting for confounders (Nakashima et al 2010). However, we did not find a reduction in EN-RAGE levels after calcitriol treatment; in fact, we observed an increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human coronary atherosclerotic plaques, a strong expression of S100A12 in smooth muscle cells and macrophages was reported (20), involving altogether S100A12 binding in the development of atherosclerosis. Similar to sRAGE levels, S100A12 levels are also elevated in patients with CKD and positively associated with IMT (21).…”
mentioning
confidence: 85%